Comparative genomics within the bacillus genus reveal the singularities of two robust Bacillus amyloliquefaciens biocontrol strains. - Magno-Pérez Bryan, María Concepción; Martínez-García, P. M.; Hierrezuelo, J.; Rodríguez-Palenzuela, P.; Arrebola-Díez, Eva María; Ramos-Rodríguez, Cayo Juan; De-Vicente-Moreno, Antonio; Pérez-García, Alejandro; Romero-Hinojosa, Diego Francisco (The American Phytopathological Society, 2015)
Bacillus amyloliquefaciens CECT 8237 and CECT 8238, formerly known as Bacillus subtilis UMAF6639 and UMAF6614, respectively, contribute to plant health by facing microbial pathogens or inducing the plant's defense mechanisms. We sequenced their genomes and developed a set of ad hoc scripts that allowed us to search for the features implicated in their beneficial interaction with plants. We define a core set of genes that should ideally be found in any beneficial Bacillus strain, including the production of secondary metabolites, volatile compounds, metabolic plasticity, cell-to-cell communication systems, and biofilm formation. We experimentally prove that some of these genetic elements are active, such as i) the production of known secondary metabolites or ii) acetoin and 2-3-butanediol, compounds that stimulate plant growth and host defense responses. A comparison with other Bacillus genomes permits us to find differences in the cell-to-cell communication system and biofilm formation and to hypothesize variations in their persistence and resistance ability in diverse environmental conditions. In addition, the major protection provided by CECT 8237 and CECT 8238, which is different from other Bacillus strains against bacterial and fungal melon diseases, permits us to propose a correlation with their singular genetic background and determine the need to search for additional blind biocontrol-related features.
Keywords: Bacillus (Bacteria) - Genética - Análisis; Bacteria; Bacillus amyloliquefaciens; Genomic analyse